Malignant "Phyllodes" tumor of the breast Communication of 3 cases - Beschizza, Victoria; Rosasco, Marianna; Episcopo, Silvia; Dorfman, Naum; Centurión, Dardo (Cirugía del Uruguay, 2003)
Three cases of «phyllode» malignant mammary tumors were studied in theAnatomo-Pathology Chair of the Montevideo, Uruguay. The discussion covered epidemiology , morphologic staging and biological significance of «phyllode» tumor within the broader spectrum of libro-epithelial breast tumors